Cluster production and the chemical freeze-out in expanding hot dense matter - D. Blaschke; S. Liebing; G. Röpke; B. Dönigus (Physics Letters B)
We discuss medium effects on light cluster production in the QCD phase diagram by relating Mott transition lines to those for chemical freeze-out. In heavy-ion collisions at highest energies provided by the LHC, light cluster abundances should follow the statistical model because of low baryon densities. Chemical freeze-out in this domain is correlated with the QCD crossover transition. At low energies, in the nuclear fragmentation region, where the freeze-out interferes with the liquid-gas phase transition, self-energy and Pauli blocking effects are important. We demonstrate that at intermediate energies the chemical freeze-out line correlates with the maximum mass fraction of nuclear bound states, in particular α particles. In this domain, the HADES, FAIR and NICA experiments can give new insights.